Strategi Pelaku Ekonomi Islam dalam Membangun Resiliensi terhadap Dinamika Ekonomi Global - Riecardy (Program Studi Ekonomi Syariah IAIN Parepare, 2025)
Economic actors play a crucial role in shaping economic systems through their activities in production, distribution, and consumption. This study examines the interdependent roles of economic actors, including households, businesses, governments, financial institutions, and foreign entities, in driving economic activities. The study also highlights the foundational principles of economic behavior, such as resource allocation, production-consumption dynamics, and exchange mechanisms, with a focus on the diverse needs of individuals and societies. Furthermore, the research explores the contributions of economic actors in fostering economic stability, growth, and global interconnectivity. By integrating theoretical perspectives and practical insights, the study provides a comprehensive understanding of how these actors interact within the framework of an economic system, particularly in the context of Islamic economic principles. The findings aim to enrich the discourse on sustainable economic development and the critical role of human and institutional participation in achieving broader economic goals.